2004
DOI: 10.1161/01.hyp.0000126579.50711.62
|View full text |Cite
|
Sign up to set email alerts
|

C242T CYBA Polymorphism of the NADPH Oxidase Is Associated With Reduced Respiratory Burst in Human Neutrophils

Abstract: Abstract-Oxidative stress contributes to the pathogenesis of atherosclerosis. p22phox -based NAD(P)H oxidases exist in the vessel wall, acting as important superoxide-generating systems in the vasculature. Some studies have identified reduced atherosclerosis in the presence of the C242T CYBA polymorphism, whereas others have not. Because vascular p22 phox is identical to neutrophil p22 phox , we studied the association between the C242T, A640G, and Ϫ930 A/G CYBA polymorphisms and the quantity of superoxide pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
0
8

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 43 publications
(35 reference statements)
8
95
0
8
Order By: Relevance
“…We could not demonstrate a consistent impact of this variant on enzyme activity. Only when restricting analysis to repeated measurements at two different study days (a subgroup of n ¼ 54 from the first study), we detected a similar effect as Wyche et al, 20 who reported about 30% less activity for the TT-allele status. In contrast, another group has reported an increased superoxide formation for the 242T allele.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We could not demonstrate a consistent impact of this variant on enzyme activity. Only when restricting analysis to repeated measurements at two different study days (a subgroup of n ¼ 54 from the first study), we detected a similar effect as Wyche et al, 20 who reported about 30% less activity for the TT-allele status. In contrast, another group has reported an increased superoxide formation for the 242T allele.…”
Section: Discussionsupporting
confidence: 85%
“…19 This finding was confirmed in neutrophilic granulocytes albeit only under stimulated conditions. 20 In marked contrast, another group observed significantly higher superoxide production in carriers of the 242T allele. 21 Gardemann et al 22 delineated an association of the 640A4G polymorphism in the 3 0 UTR of CYBA with cardiovascular arterial disease, in particular in hypertensives.…”
Section: mentioning
confidence: 95%
See 1 more Smart Citation
“…Accordingly, we found similar results for the C2 response across the genotypes, with a significant difference observed between AA and GG/AG carriers. But MaciasReyes et al 10 found opposite results, whereas Wyche et al 12 failed to find any relationship. Accordingly, associations between the rs1049255 polymorphism and vascular complications have been contradictory.…”
Section: Discussionmentioning
confidence: 92%
“…Among these, rs1049255 (A640G) has been widely discussed in the context of cardiovascular diseases; however, the results have been conflicting. [9][10][11][12] For rs7195830, there have been few studies related to cardiovascular diseases. Rather, rs7195830 has been mentioned in studies on non-Hodgkin lymphoma and cervical cancer as an oxidative stress-related locus.…”
Section: Introductionmentioning
confidence: 99%